PEMELIHARAAN IKAN LELE DUMBO (CLARIAS GARIEPINUS) PADA KOLAM BETON - ANNISA, KARIMA NUR; AFFANDI, RANGGA IDRIS (GANEC SWARA, 2024)
African catfish (Clarias gariepinus) is a type of freshwater fish that can grow and develop well because it can be cultivated on limited land. Currently, African catfish cultivation has developed rapidly because the cultivation and marketing technology is relatively easy for the community, and the funding required is relatively small. Catfish has advantages compared to other fish, namely faster growth, economical price and high nutritional content. Catfish is a type of consumption fish that has promising prospects because it has a fairly high level of market uptake. This research aims to determine the performance of African catfish cultivation in concrete ponds. This research activity was carried out in June-July 2023 at the Lingsar Fish Seed Center (BBI), West Lombok, West Nusa Tenggara. The data collection techniques used in this research were descriptive methods and field observations. The results obtained are that African catfish cultivation activities include pond preparation, selection and stocking of seeds, the grow-out process where this grow-out process includes feed management, water quality management and health management of African catfish. Next, growth observations were carried out where growth for 21 days could provide significant results, which can be seen from the absolute weight and length obtained, namely 1.101 grams and a length of 6.3 cm. Previously, the initial average weight of farmed fish was 5.4 grams. After 21 days of rearing, the final average weight was 18.6 grams. Then the FCR value obtained was 0.8 and SR 88%. Meanwhile, for optimal maintenance water quality, the maintenance temperature range is around 26-28°C, pH is around 6.6-8.2 and DO is around 47.5-9.8 mg/l. From these data it can be said that catfish cultivation has been successful